\[
a_n = a_1 + (n – 1) d
\]
Where:

$a_n$ = the $n^{th}$ term in the sequence

$a_1$ = the first term of the sequence

$d$ = the common difference between terms

\[ S_n = \frac{n}{2}[2a_1 + (n – 1) d] \] \[ S_n = \frac{n}{2}(a_1 + a_{last}) \] Where:

$n$ = the number of terms

$a_1$ = the first term of the sequence

$d$ = the common difference between terms

$a_{last}$ = the last term of the sequence

$a_n$ = the $n^{th}$ term in the sequence

$a_1$ = the first term of the sequence

$d$ = the common difference between terms

**Sum of Arithmetic Progression:**\[ S_n = \frac{n}{2}[2a_1 + (n – 1) d] \] \[ S_n = \frac{n}{2}(a_1 + a_{last}) \] Where:

$n$ = the number of terms

$a_1$ = the first term of the sequence

$d$ = the common difference between terms

$a_{last}$ = the last term of the sequence